Future expectation levels of adolescents during the COVID-19 pandemic - Küçükkelepçe, Osman; Parlak, Mehmet Emin; Öz, Erdoğan; Kapıcı, Yaşar; Ener, Dilek (Frontiers in Public Health, 2023)
Introduction This study was aimed at examining the future expectations of high school students during the COVID-19 pandemic. Methods A future expectation questionnaire was administered to 412 high school students, and the change in their expectations for the future during the COVID-19 pandemic period was questioned in this questionnaire. Results Scale sub-scores and total scores of those who were infected with COVID-19 were significantly lower than those who were not (p < 0.001). The scale sub-scores and total scores of those whose relatives were infected with COVID-19 were significantly lower than those who were not (p < 0.05). The scale sub-scores and total scores of those who think that the pandemic will always continue, those who think that their education is disrupted due to the pandemic, those who think that the pandemic affects their choice of profession, and those who express that they look to the future with more hope than before the pandemic were found to be significantly lower (p < 0.05). Discussion The future expectation is a more sensitive concept among adolescents than adults. During and after the pandemic, activities should be organized by considering the sensitivity of young people about their future expectations, and families and society should be made aware of this issue.